Modeling surface tension in compressible flow on an adaptively refined mesh. (15th July 2019) - Jibben, Z.; Velechovsky, J.; Masser, T.; Francois, M.M.
Abstract: We present a numerical approach to model surface tension between immiscible materials within an inviscid compressible flow solver. The material interface is represented using the volume of fluid technique with piecewise-linear interface reconstructions. We employ the continuum surface force to model surface tension, and have implemented it in the context of the MUSCL-Hancock finite volume method for the Euler equations on an adaptively refined Eulerian mesh. We show results from droplet verification tests, the Rayleigh–Taylor instability linear regime, and simulate a 2D shock–droplet interaction.